2023
DOI: 10.7759/cureus.47967
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cutting Seton Technique in Treating High Anal Fistula

Asim M Almughamsi,
Mohamed Khaled S Zaky,
Abdullatif M Alshanqiti
et al.

Abstract: Objectives Fistula-in-ano is a common condition that negatively affects the quality of life of its sufferers. A high anal fistula poses a significant challenge for surgeons due to its proximity to the anorectal ring and the potential risk of incontinence rather than recurrence. Many modalities have been used in a justified search for a satisfactory cure for the condition, but the seton remains a mainstay of surgical treatment. Therefore, the rationale of this study is to assess the outcome of treati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Despite developing different surgical techniques to treat perianal fistulas, it is still a major medical issue. Recently, some novel treatment methods for managing perianal fistula have been proposed, which rely on the surgeon's skills, experience, and the complexity of the fistula, all of which contribute to the success of these procedures 23 . Despite this, studies have revealed that they have disadvantages compared with traditional treatments, along with being less cost‐effective 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite developing different surgical techniques to treat perianal fistulas, it is still a major medical issue. Recently, some novel treatment methods for managing perianal fistula have been proposed, which rely on the surgeon's skills, experience, and the complexity of the fistula, all of which contribute to the success of these procedures 23 . Despite this, studies have revealed that they have disadvantages compared with traditional treatments, along with being less cost‐effective 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, studies have revealed that they have disadvantages compared with traditional treatments, along with being less cost‐effective 24 . However, these various techniques can be employed to treat high fistulas, cutting setons still playing an important role 23 . A seton drainage procedure may be the best option in cases of multiple previous surgeries, compared to other procedures, which are potentially challenging and complicate the patient's current situation.…”
Section: Discussionmentioning
confidence: 99%